FLOOD MODEL FOR THE BÓDVA CATCHMENT - RÓBERT NÉMETH; ENDRE DOBOS (Acta Geographica Debrecina. Landscape & Environment Series)
In term of floods the current area of Hungary has extensively been endangered. Modelling of flood processes – mainly following the hydrological events in the riverbed – has recently been developed. As far as protection dykes provide protection of the inhabited and agricultural areas, the flood models can run with acceptable preciseness. However, when dykes cannot withstand against the increasing load and a dyke burst occurs, fast and efficient protection measures shall be taken in the protected areas. The dynamic 4D Flood model presented in this paper makes possible a fast modelling of dyke burst occurring in the protected side and spreading of water mass, based on real parameters. For this reason the features of protected area shall be recognised, for example topology of creeks, features of agricultural and inhabited areas, parameters of roads, railways, rainwater drainage, buildings, natural conditions (soil parameters, meteorological characteristics, etc.). The results satisfy the comprehensive demands of the Directorate General for Disaster Prevention of Borsod-Abaúj-Zemplén County. In case of dyke burst, the completed Flood Model can run the expected events of the next hour in a few minutes. This time is enough for the specialists to bring operative decisions to protect the inhabitants and avoid material losses.